PENERAPAN MODEL PBL, NMM DAN PERMAINAN ULAR TANGGA DALAM MENINGKATKAN KETERAMPILAN BERPIKIR KRITIS DAN HASIL BELAJAR PADA MUATAN IPAS KELAS V SDN BENUA ANYAR 10 BANJARMASIN - Sayling Sansan Septemercy; Zain Ahmad Fauzi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study was motivated by the low levels of students’ critical thinking skills and learning outcomes, which were caused by one-way teaching and a lack of variety in instructional methods. The purpose of this study was to describe students’ critical thinking skills and learning outcomes. The research employed Classroom Action Research (CAR) over the course of three sessions, involving 15 fifth-grade students at SDN Benua Anyar 10 Banjarmasin. Data were collected through observation and tests. The results showed a significant improvement in each session: critical thinking skills increased from 33% in the first session to 87% in the third session, categorized as "Almost All Highly Skilled," and learning Outcomes increased from 53% to 100%. These findings overall indicate that the implementation of the PBL model, NMM, and the Snakes and Ladders game effectively enhanced students’ critical thinking skills and learning outcomes.